2015
DOI: 10.1016/s2214-109x(15)00011-x
|View full text |Cite|
|
Sign up to set email alerts
|

Global epidemiology of yaws: a systematic review

Abstract: SummaryBackgroundTo achieve yaws eradication, the use of the new WHO strategy of initial mass treatment with azithromycin and surveillance twice a year needs to be extended everywhere the disease occurs. However, the geographic scope of the disease is unknown. We aimed to synthesise published and unpublished work to update the reported number of people with yaws at national and subnational levels and to estimate at-risk populations.MethodsWe searched PubMed and WHO databases to identify published data for prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 19 publications
3
64
1
Order By: Relevance
“…Studies in the Pacific have found a seroprevalence of antitreponemal antibodies of >30% in several communities ( 7 , 17 ) and a prevalence of clinical yaws of ranging from 2.5% to 5% in communities before mass treatment. The prevalence of yaws is markedly lower in many yaws-endemic countries in West Africa ( 20 ), but limited community-based seroprevalence data are available to inform our understanding of disease transmission there. …”
Section: Discussionmentioning
confidence: 99%
“…Studies in the Pacific have found a seroprevalence of antitreponemal antibodies of >30% in several communities ( 7 , 17 ) and a prevalence of clinical yaws of ranging from 2.5% to 5% in communities before mass treatment. The prevalence of yaws is markedly lower in many yaws-endemic countries in West Africa ( 20 ), but limited community-based seroprevalence data are available to inform our understanding of disease transmission there. …”
Section: Discussionmentioning
confidence: 99%
“…[4] Chronic skin ulcers that fail to heal are a common presentation for all three: BU, CL, and yaws (Fig 1). [2,3,6] Skin ulcers may also result from polymicrobial infections, Haemophilus ducreyi ,[13] and neuropathy (due to leprosy, diabetes) or vascular disease. Lower limb swelling of filarial lymphoedema may be mistaken for podoconiosis, TB lymphadenitis, or systemic diseases such as heart failure (Fig 2).…”
Section: Description Of Integrated Idm Ntd Implementationmentioning
confidence: 99%
“…Yaws is an infectious disease that causes disfiguring and often painful lesions of the skin and bones. Although data are limited, it is thought to be endemic in at least 13 countries, including three in the Pacific[3]. …”
Section: Introductionmentioning
confidence: 99%